PSYCHOLOGICAL ADVICE ABOUT THE RELATIONSHIP OF HUSBAND AND WIFE IN THE FAMILY - Mamayusupova Iroda Khamidovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the issue of men and women in the family and the moments in which the most problems arise, as well as the fact that family and marriage relations are considered a sacred bond in our religion. Information is given about the great purposes of tying bonds and building a family.